Preliminary Study on Movement of Available Water in Sandy Loam Soils Under Dry Farming Conditions - Dayal, Rajbans; Singh, Akshayaber; Saraf, N H (Annals of Arid Zone, 2016)
The study on availability of moisture under dry farming conditions in relation to time of planting/sowing. reveals that the crops planted in the early stages of rainfall provides better utilization of moisture and its availability during the crop growth. Late planting has shown that there is a daficit of moisture in the effective root zone at the later stage of crop growth which results in low yield.